2018
DOI: 10.1016/j.jcrc.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Bereaved donor families' experiences of organ and tissue donation, and perceived influences on their decision making

Abstract: The influence of temporality on donation-decision making is worthy of consideration in the planning of future education, policy, practice, and research for improved rates of family consent to donation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 28 publications
2
61
0
3
Order By: Relevance
“…This is a novel observation, but has been hinted at in existing research. 34 The current study supports the use of shared decisionmaking with ICU staff and families when considering donation, [9][10][11][12] and suggests that efforts to motivate and engage ICU staff in donation may be more effective if framed in terms of how it benefits families. Conversely, policies and practices that increase donation activity but negatively impact families (e.g., withdrawal of life support in the operating room to shorten ischemic time) are unlikely to receive support from ICU staff.…”
Section: Suggested Practices Align With Those Reported Elsewheresupporting
confidence: 64%
See 1 more Smart Citation
“…This is a novel observation, but has been hinted at in existing research. 34 The current study supports the use of shared decisionmaking with ICU staff and families when considering donation, [9][10][11][12] and suggests that efforts to motivate and engage ICU staff in donation may be more effective if framed in terms of how it benefits families. Conversely, policies and practices that increase donation activity but negatively impact families (e.g., withdrawal of life support in the operating room to shorten ischemic time) are unlikely to receive support from ICU staff.…”
Section: Suggested Practices Align With Those Reported Elsewheresupporting
confidence: 64%
“…Organ donation rates vary across comparable intensive care units (ICUs), 1 suggesting that donation processes differ between ICUs, despite the existence of clinical guidelines for donor care, 2,3 and the coordination efforts of organ donation organizations (ODOs). Aiming to improve donation rates, many studies have examined donor family [4][5][6][7][8][9] and ICU staff [10][11][12] experiences with donation decision-making. Comparatively fewer studies have examined the wider process of donor care in the ICU.…”
Section: Résumémentioning
confidence: 99%
“…The long length of time for donation is high among the reasons for families of eligible cDCD patients choosing to decline consent/authorization . Sque et al identified family distress because of watching and waiting for death to occur. Similarly, discomfort regarding prolonged dying while seeking potential recipients was a source of discomfort for parents who consented to donate their child's organs after circulatory determination of death .…”
Section: Case Analysis and Discussionmentioning
confidence: 99%
“…Studies involving families of cDCD donors have shown a need for reassurance that their relative will be cared for with respect both during and after the removal of organs and/or tissues for donation . The family were asked if they would like to wait at the hospital to see R following organ and tissue donation surgery.…”
Section: Case Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation